2022
DOI: 10.1039/d2ra01851a
|View full text |Cite
|
Sign up to set email alerts
|

First principles study of optoelectronic and photocatalytic performance of novel transition metal dipnictide XP2 (X = Ti, Zr, Hf) monolayers

Abstract: Low cost and highly efficient two dimensional materials as photocatalysts are gaining much attention to utilize solar energy for water splitting and produce hydrogen fuel as an alternative to deal with the energy crisis and reduce environmental hazards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Similar trends have also been predicted theoretically in the published studies. 44,45,[59][60][61]75,76 These ndings revealed that BAs-SiS and BP-SiS vdW heterostructures are promising candidates for applications in photovoltaics and photocatalytic water splitting.…”
Section: Papermentioning
confidence: 99%
“…Similar trends have also been predicted theoretically in the published studies. 44,45,[59][60][61]75,76 These ndings revealed that BAs-SiS and BP-SiS vdW heterostructures are promising candidates for applications in photovoltaics and photocatalytic water splitting.…”
Section: Papermentioning
confidence: 99%
“… 13 Recently, Janus WSSe monolayers have been fabricated through the CVD method. 14 The MXY (M = Mo, W; X, Y = S, Se) monolayers have proven excellent electronic and optical properties, realizing them potential candidates for designing optoelectronic, 15 piezoelectric, 16 photocatalysis, 17 and spintronic devices. 18 More recently, it has been demonstrated that all single layer Janus CrXY (X, Y = S, Se, Te) are energetically and thermally stable, and display semiconducting band gap nature (in the range of 1.10–1.57 eV), have good optical absorption in the near infra-red region and hold a suitable band edge for fully photocatalytic water splitting.…”
Section: Introductionmentioning
confidence: 99%